2011
DOI: 10.1149/1.3534796
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Performance of Carbon Steel in Simulated Pore Solution in the Presence of Micelles

Abstract: This study presents the results on the investigation of the corrosion behavior of carbon steel in model alkaline medium in the presence of very low concentration of polymeric nanoaggregates ͓0.0024 wt % polyethylene oxide ͑PEO͒ 113 -b-PS 70 micelles͔. The steel electrodes were investigated in chloride-free and chloride-containing cement extracts. The electrochemical measurements ͑electrochemical impedance spectroscopy and potentiodynamic polarization͒ indicate that the presence of micelles alters the compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 86 publications
4
24
0
Order By: Relevance
“…In cement extract [24], a very low concentration of the micelles in the corrosion medium (0.0024 wt%) is able to initially increase the corrosion resistance of the carbon steel in the presence of 1% NaCl and the pronounced effect only appeared at early stages, which was as expected to some extent, considering the very low concentration of micelles used. At early stages, the micelles adsorbed on the steel surface and altered the morphology and chemical composition of the formed products, a more uniform and compact layer, i.e., with increased barrier properties.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…In cement extract [24], a very low concentration of the micelles in the corrosion medium (0.0024 wt%) is able to initially increase the corrosion resistance of the carbon steel in the presence of 1% NaCl and the pronounced effect only appeared at early stages, which was as expected to some extent, considering the very low concentration of micelles used. At early stages, the micelles adsorbed on the steel surface and altered the morphology and chemical composition of the formed products, a more uniform and compact layer, i.e., with increased barrier properties.…”
Section: Introductionsupporting
confidence: 54%
“…The expectation results from the fact that in the presence of micelles, the reduced permeability [22,25] will lead to a reduced chloride penetration and corrosion initiation, respectively, will be delayed. Further, in the event of chloride arrival at the steel/cement paste interface, the presence of micelles would even further halt corrosion propagation due to maintained superior properties of the passive layer (as this was observed for earlier stage in model liquid environment, [24]). To this end, this article reports on the integration of electrochemistry and concrete material science for a thorough evaluation of a reinforced mortar system modified with the same type of micelles (PEO 113 -b-PS 70 ) in comparison to non-modified such in control (non-corroding) and corroding conditions.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In our previous research, the influence of polymeric micelles and vesicles (with a hydrodynamic radius of 50 nm and 220 nm) respectively on the corrosion performance of reinforced concrete was investigated (Hu et al 2012b(Hu et al , 2011(Hu et al , 2012c. Micelles are polymeric, self-assembled nano-architectures with amphiphilic properties in our case, whereas vesicles are nano-sacs, that enclose a volume, containing water or chosen substances.…”
Section: Introductionmentioning
confidence: 99%
“…Initial tests in simulated pore solution (Hu et al 2011) and reinforced mortar in the presence of micelles (Hu et al 2012b) proved that corrosion initiation was delayed on one hand and chloride binding capacity of the mortar was increased on the other. Further investigations on admixed vesicles, and especially Ca-containing ones, where saturated Ca(OH) 2 solution was pre-reserved in their core, (Hu et al 2012c) indicated "self-healing" effect of the corrosion damage in the reinforcement: after corrosion initiation, the steel corrosion resistance was significantly increased and corrosion propagation on the steel reinforcement was halted.…”
Section: Introductionmentioning
confidence: 99%